Assessment of heavy metal pollution in surficial sediments from a tropical river-estuary-shelf system: A case study of Kelantan River, Malaysia - Wang, Ai-jun; Bong, Chui Wei; Xu, Yong-hang; Hassan, Meor Hakif Amir; Ye, Xiang; Bakar, Ahmad Farid Abu; Li, Yun-hai; Lai, Zhi-kun; Xu, Jiang; Loh, Kar Hoe (Elsevier, 2017)
To understand the source-to-sink of pollutants in the Kelantan River estuary and the adjacent shelf area in Malaysia, a total of 42 surface sediment samples were collected in the Kelantan River-estuary-shelf system to analyze for grain size, total organic carbon (TOC) content, Al and heavy metals (Cr, Ni, Cu, Zn, Cd and Pb). The surficial sediments were mainly composed of clayey silt and the TOC content in sediments decreased from the river to the shelf. The surficial sediments experienced Pb pollution; Cr only showed a certain level of pollution in the coastal area of the estuary but not in other areas, and Ni, Cu, Zn, and Cd showed no pollution. The heavy metals mainly originated from natural weathering and erosion of rocks and soils in the catchment and enriched near the river mouth. Total organic carbon can promote the enrichment of heavy metals in sediments.